Using Facebook to Recruit People with Dwarfism: Pros and Pitfalls for Disabled Participants and Researchers - Erin Pritchard (Scandinavian Journal of Disability Research, 2021)
Social networking sites have gained widespread popularity and remain a popular way of keeping in contact with others. Drawing on networked individualism, this paper argues that Facebook is beneficial for recruiting disabled participants spread over a wide geographical area. The aim of the article is to provide a comparison between using Facebook as a recruitment tool and the more traditional form of face-to-face recruitment via attending events for people with dwarfism. These were the two main forms of recruitment used to understand how people with dwarfism navigate through public spaces. This paper argues that Facebook is not just good for recruiting disabled participants, but also for disabled researchers to use as an accessible form of recruitment. However, building on recruitment experiences, including those influenced by a digital divide, this paper demonstrates that caution must be taken when trying to recruit participants using Facebook alone. This paper offers recommendations for researchers considering using Facebook as a recruitment tool.